2021
DOI: 10.1051/0004-6361/202039742
|View full text |Cite
|
Sign up to set email alerts
|

Searching for the 1 mHz variability in the flickering of V4743 Sgr: A cataclysmic variable accreting at a high rate

Abstract: Aims. A few well studied cataclysmic variables (CVs) have shown discrete characteristic frequencies of fast variability; the most prominent ones are around log(f/Hz) ≃ −3. Because we still have only small number statistics, we obtained a new observation to test whether this is a general characteristic of CVs, especially if mass transfer occurs at a high rate typical for dwarf nova in outbursts, in the so called high state. Methods. We analysed optical Kepler data of the quiescent nova and intermediate polar V4… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…With the result obtained with the XMM-Newton data we draw the conclusions that CAL 83 has a variable period, ruling out that the observed LS periodogram is modulated by a stable period with variable amplitude (even if also the amplitude varies). As mentioned above, Dobrotka et al (2021) were able to model the periodogram of Nova LMC 2009a in the SSS phase even only with variable amplitude, but a variable period appeared to yield better simulations. While in the LMC 2009a the scattering was around 0.4 s, in CAL 83 it is quite longer, namely 2.1 s, allowing a more definite conclusion.…”
Section: Simulating the Cal 83 Data For Better Understandingmentioning
confidence: 86%
“…With the result obtained with the XMM-Newton data we draw the conclusions that CAL 83 has a variable period, ruling out that the observed LS periodogram is modulated by a stable period with variable amplitude (even if also the amplitude varies). As mentioned above, Dobrotka et al (2021) were able to model the periodogram of Nova LMC 2009a in the SSS phase even only with variable amplitude, but a variable period appeared to yield better simulations. While in the LMC 2009a the scattering was around 0.4 s, in CAL 83 it is quite longer, namely 2.1 s, allowing a more definite conclusion.…”
Section: Simulating the Cal 83 Data For Better Understandingmentioning
confidence: 86%
“…This QPO is exceedingly weak, appearing only in three bins of the PDS. Scientists already hypothesized that most binary star systems exhibit a similarly subtle QPO at the frequency mentioned earlier [16][17][18]. To accurately describe our data, we need to identify a model that fits our observations.…”
Section: Signal Processing Timing Analysismentioning
confidence: 97%
“…For example, a handful of variable stars with periods < 90 minutes are found among ∼10 million variable candidates in the ZTF survey (Ofek et al 2020) and a few dozen M dwarf flares are found in four years of ASAS-SN transient alerts (Schmidt et al 2019). They miss classes such as double white dwarf binaries with periods down to ∼5 minutes (Kruckow et al 2021), transiting planets with periods down to ∼4 hr (Smith et al 2018), magnetic reconnection flares with durations from minutes to hours (Namekata et al 2017), and stochastic flickering in CV disks with characteristic timescales of around 1000 s (Dobrotka et al 2021).…”
Section: Introductionmentioning
confidence: 99%